HUBUNGAN KUALITAS PELAYANAN KESEHATAN TERHADAP TINGKAT KEPUASAN PASIEN PESERTA BPJS MANDIRI DI PUSKESMAS DELITUA KABUPATEN DELI SERDANG TAHUN 2018 - Selamat Ginting; Adi Arianto (Fakultas Keperawatan Institut Kesehatan Deli Husada, 2019)
Health is a prosperous state of the body, soul, and social which is very possible for every individual to live productively in a social and economic way. Tests of research are to identify the relationship between the quality of health services to the level of satisfaction of BPJS Mandiri in Public Health Center Deli Tua Kab Deli Serdang. The research method uses an analytical survey type with a sample of 95 people. The results of the study are that there is a significant relationship between Tangible, reliability, responsiveness, assurance, empathy for the satisfaction of BPJS Mandiri in Public Health Center Deli Tua Kab Deli Serdang wit p-value(0.00). The conclusion in this study is that the most dominant factors affecting patient satisfaction are direct evidence of this indicated by the highest Exp (B) of 6,374